Inside Back Cover: Accelerating Diffusion‐Ordered NMR Spectroscopy by Joint Sparse Sampling of Diffusion and Time Dimensions (Angew. Chem. Int. Ed. 25/2014). Issue 25 (6th May 2014) - Urbańczyk, Mateusz; Koźmiński, Wiktor; Kazimierczuk, Krzysztof
Abstract : Diffusion‐ordered NMR spectroscopy is an effective method for the analysis of chemical mixtures. However, its resolution is often not sufficient for unambiguous spectral assignment. Multidimensional spectroscopy may enhance the resolution, but is rarely employed in diffusion‐ordered NMR spectroscopy because of lengthy sampling of a signal. In their Communication on page 6464 ff., K. Kazimierczuk et al. show how the measurement can be accelerated by exploiting the principles of compressed sensing.